2009
DOI: 10.1038/eye.2008.404
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal injection of bevacizumab for myopic choroidal neovascularization: 1-year follow-up

Abstract: Purpose To evaluate the safety and efficacy of intravitreal bevacizumab in Chinese patients with choroidal neovascularization (CNV) secondary to pathologic myopia. Methods Eight eyes of consecutive patients with myopic CNV without earlier treatment were treated with intravitreal injection of bevacizumab (2.5 mg). All patients underwent a clinical examination, which included visual acuity measurements, fundus photography, fluorescein angiography, and optical coherence tomography. Results Eight eyes of eight pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 9 publications
0
20
1
2
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, the follow-up periods were up to 1-year in most of the earlier studies. There have been a few studies that showed 2-years visual outcomes of IVB for mCNV, and the results have been conflicting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, the follow-up periods were up to 1-year in most of the earlier studies. There have been a few studies that showed 2-years visual outcomes of IVB for mCNV, and the results have been conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…6 Because of the poor natural history of mCNVs, several procedures have been tried to treat mCNVs, for example, thermal laser photocoagulation, 7 photodynamic therapy (PDT) with verteporfin (Visudyne, Novartis Pharma AG, Basel, Switzerland), 8 and intravitreal bevacizumab (Avastin; Genentech, South San Francisco, CA, USA), a recombinant humanized monoclonal anti-VEGF antibody. Earlier case series have reported good visual outcomes 1 to 2 years after intravitreal bevacizumab (IVB), [9][10][11][12][13][14][15][16][17][18][19][20][21] and at present IVB would be the first-line therapy for sub-and juxtafoveal mCNVs. 22 However, there is still not enough information to predict the visual outcome of each patient with mCNV treated with IVB.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Treatment outcomes after intravitreal bevacizumab in 15 studies are summarised in Table 1. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] A cumulative analysis of all study data reveals the following trends. Of all studies examined, a total of 181 eyes received treatment for naïve lesions, and 74 eyes were treated earlier.…”
Section: Pathological Myopiamentioning
confidence: 99%
“…4,6,[21][22][23][24][25] A terapêutica antiangiogénica, nomeadamente o bevacizumab e o ranibizumab, estão aprovados para o tratamento da neovascularização coroideia secundária à degenerescência macular da idade (DMI), tendo também mostrado claros benefícios clínicos na neovascularização associada a outras situações de causa inflamatória ou vascular. 3,9,26 Face à evidência de eficácia e segurança com o uso destes agentes, a sua utilização na NVC associada à miopia patológica é atualmente considerada terapêutica de primeira linha. [2][3][4]11,26 O ranibizumab e o bevacizumab são anticorpos monoclonais antiangiogénicos utilizados no tratamento da neovascularização coroideia, com resultados favoráveis a curto prazo.…”
Section: Introductionunclassified
“…3,9,26 Face à evidência de eficácia e segurança com o uso destes agentes, a sua utilização na NVC associada à miopia patológica é atualmente considerada terapêutica de primeira linha. [2][3][4]11,26 O ranibizumab e o bevacizumab são anticorpos monoclonais antiangiogénicos utilizados no tratamento da neovascularização coroideia, com resultados favoráveis a curto prazo. 9,27 Estudos recentes demonstraram resultados benéficos e sustentados da terapêutica com bevacizumab na NVC miópica, 28,29 estando em curso ensaios clínicos randomizados e multicêntricos para avaliar a eficácia do ranibizumab a longo prazo.…”
Section: Introductionunclassified